(untitled) (SIRJANĀ – A Journal Of Arts and Art Education, 2021)
Batsa Gopal Vaidya’s paintings integrate primordial images, symbols, and figures from myths, cultures, and rituals. These images and symbols are the archetypes that appear recurrently in his artworks. The artist shares these primordial images from his collective unconscious, the common heritage of mankind, and the storehouse of archetypes that reappear in the creative process. They suggest the pattern of experiences of our ancestors. These recurring communicable images function as an aesthetic mode of communication in society. Swastika, shaligram, tilaka, the Himalaya, rivers, various deities, and their attributes are such images and symbols that do not only provide aesthetic pleasure but also take the viewers back to their cultural roots, rituals, and myths. This article attempts to trace the archetypes in Vaidya’s works and explain their significances.